The thermal degradation of epoxy resins 4: the thermal degradation of polypyromellitimides 2 - Bishop, D. P. (College of Aeronautics, 1968)
A summary of work carried out between 1st September, 1967 and 1st March, 1963 on the thermal degradation of the resin hardener systems DEM/EP274, DDM/KOPDX171, PA/EP274, PA/KOPDX171, THPA/EP274, PMDA/EP274.